THE DEVELOPMENT AND EDUCATION OF NATIONAL CHARACTERS IN YOUTH ON REPRESENTATIVES OF OUR HEROES IS A PRIORITY PROBLEM - Musurmonova Maludakhon (Web of Journals Publishing, 2023)
This article provides information on the principles of good morals in the process of raising our ancestors and instilling national virtues into the minds of our youth.
Keywords: Intelligence, perception, manners, maturity, perfection, spiritual, humanity, emotions.